Il mito di Elena​ e il potere controverso della bellezza.​ Un percorso intertestuale tra Omero, Euripide, Stesicoro, Gorgia, Isocrate e Platone - Fulvia De Luise (Peitho)
The myth of Helen runs through the poetic and philosophical tradition of the ancient world. Her defense is a paradox for legal tradition and the opportunity for a triumph of rhetoric. Through her name Greeks discuss the enchantment of beauty and desire as a driving force, which can have a destructive or constructive effect, or even act as a medium for great ideals. With Helen, a controversial power is at issue, which emanates from beauty and which presents itself differently to the gaze of men and women, raising a “gender” question that has clear traces in ancient texts. All this gives reason to appreciate, once again, the usefulness of intertextual comparison to investigate themes transversally present in poetic, rhetorical, legal, historical and philosophical texts. The revisiting of myths is already an elective place for a consciously intertextual practice on the part of tragic poets, in which Plato finds a model for his philosophical theatre. Among the detectable intersections, it still deserves investigation that precisely the “rewriting (palinodia)” of the myth of Helen offers Plato the opportunity to introduce a decisive turning point in the Phaedrus, where his Socrates deals with the power of eros by dueling with rhetoric: here a poetic quotation becomes a philosophical place, in which the threads of a distant comparison, sometimes explicit, sometimes underground, intertwine between the intellectuals active in the first half of the 4th century. The ambiguity of the myth of Helen is the underlying theme of this essay, which aims to identify connections between the texts and implications that are not always declared. The themes examined are the praise or denigration connected to the image of Helen in Homer, the double rewriting of the myth in Euripides (The Trojan women and Helen), the different virtuosities of its defense in Stesichorus, Gorgias and Isocrates, the philosophical metamorphosis of the myth in Plato’s Phaedrus, where for the first time the quality of desire is questioned together with the type of love that derives from it. This essay is intended to be a tribute to Livio Rossetti, who made intertextual study an indispensable exegetical model for understanding what is talked about in the literature of the ancient world.